Pengaruh Workplace Sprituality dan Self Esteem terhadap Intention to stay dengan Employee Engagement sebagai Variabel Mediasi pada Guru Yayasan Adzkia Sumatera Barat - Kurniawan Effendi, Arya; Games, Donard; Rivai, Harif Amali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
This study aims to determine and analyze how much influence workplace spirituality and self-esteem have on the intention to stay with Employee engagement as a Mediating Variable. In other words, high employee engagement can make teachers stay on their jobs. The approach that will be used in this study is quantitative research. The results of the study also revealed that teacher engagement in work does not have a significant direct relationship with their intention to stay. This shows that although engagement is important, other factors such as work spirituality have a greater role. Therefore, the Adzkia Foundation of West Sumatra needs to prioritize spirituality factors in creating a work environment that can encourage teacher loyalty to continue working at the foundation.